Pan-cancer analysis of forkhead box Q1 as a potential prognostic and immunological biomarker - Dong, Qiguan; Yan, Lirong; Xu, Qingbang; Hu, Xianliang; Yang, Yan; Zhu, Ruiwu; Xu, Qian; Yang, Yuchao; Wang, Bengang (Frontiers in Genetics, 2022)
Forkhead box Q1 (FOXQ1) is a member of the forkhead transcription factor family involved in the occurrence and development of different tumours. However, the specific expression patterns and functions of FOXQ1 in pan-cancer remain unclear. Accordingly, we collected the expression, mutation and clinical information data of 33 tumours from TCGA database. Via public pan-cancer transcriptome data analysis, we found that FOXQ1 is differentially expressed in various tumours at tissue and cell levels, such as liver hepatocellular carcinoma, colon adenocarcinoma, lung adenocarcinoma, lung squamous cell carcinoma, thyroid carcinoma and kidney renal clear cell carcinoma. Kaplan-Meier and Cox analyses suggested that FOXQ1 expression was associated with poor overall survival of cutaneous melanoma and thymoma. Its expression was also associated with good disease-specific survival (DSS) in prostate adenocarcinoma but poor DSS in liver hepatocellular carcinoma. In addition, FOXQ1 expression was associated with poor disease-free survival of pancreatic adenocarcinoma. Moreover, FOXQ1 expression was closely related to the tumour mutational burden (TMB) in 14 tumour types and microsatellite instability (MSI) in 8 tumour types. With an increase in stromal and immune cells, FOXQ1 expression was increased in breast invasive carcinoma, pancreatic adenocarcinoma, thyroid carcinoma, lung adenocarcinoma and ovarian serous cystadenocarcinoma, while its expression was decreased in pancreatic adenocarcinoma, bladder urothelial carcinoma and stomach adenocarcinoma. We also found that FOXQ1 expression was related to the infiltration of 22 immune cell types in different tumours (P<0.05), such as resting mast cells and resting memory CD4 T cells. Finally, FOXQ1 was co-expressed with 47 immune-related genes in pan-cancer (P<0.05). In conclusion, FOXQ1 expression is closely related to prognosis, clinicopathological parameters, cancer-related pathway activity, the TMB, MSI, the tumour microenvironment, immune cell infiltration and immune-related genes and has the potential to be a diagnostic and prognostic biomarker as well as an immunotherapy target for tumours. Our findings provide important clues for further mechanistic research into FOXQ1.